MAKNA KEBANGKITAN MENURUT 1 KORINTUS 15 DAN APLIKASINYA BAGI ORANG PERCAYA MASA KINI - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Sekolah Tinggi Teologi Duta Panisal, 2021)
In the history of Christ's resurrection, it is told about the efforts of certain groups who tried to distort the news of Jesus' resurrection, even now there are still people who doubt the resurrection of Jesus Christ, including those who claim to be Christians. For this reason, one of the aims of this writing is: First, to reveal and correct the wrong view of the resurrection. Second, describe the true meaning of the resurrection based on 1 Corinthians 15:1-58. Third, explain the application of the meaning of resurrection to believers today. The writing method used in writing this journal uses a descriptive literature method. The conclusion that can be drawn is how Christians must apply at least three things, namely: First, Stand Firm Because There Are Promises and Guarantees. Second, use the body today for the glory of God. Third, Trying to Convince Others.